Narrativer fra ledere i Kulturdag - et samarbeidsprosjekt mellom grunnskole og kulturskole - Fostad, Ingrid (Nordic Journal of Comparative and International Education (NJCIE), 2023)
As early as the 1980s, there was a policy intention for collaboration between the Schools of Music and Performing Arts (SMPA) and the primary schools in Norway. Since then, several policy documents have defined collaboration between the SMPAs and the primary schools. Kulturdag [Cultural Day] is a project in which a municipality in Norway tries to meet the desire for cooperation between the SMPAs and primary schools in arts education. Kulturdag exists in 17 schools in this municipality (2022/2023). The Kulturdag project is complex, constantly expanding, and involves many people in different roles. This study examines the leadership perspective by focusing on one primary school with Kulturdag. The question I have explored is: How can Kulturdag be understood through the stories of the SMPA and primary school leaders in the light of practice architecture theory? The methods used to collect the data were ethnographically inspired, and the leaders' stories were interpreted from the researcher's position using narrative thematic analysis and the theory of practice architectures. This study is a practical and scientific contribution to educational research, providing more knowledge about the leadership perspective in a primary school-SMPA cooperation. One of the key findings is that this collaboration is based on a systemic change in primary music education - from traditional one-teacher music education to a change in practice architecture that allows for more teachers, diverse teaching, and staff participation in Kulturdag.